(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: the main purpose of our work was to experimentally substantiate and develop the base carrier for a low-level pH foam-washing agent. Materials and Methods: The determination of foaming ability was carried out by means of the Ross-Miles Foam Test apparatus as a standard device for measuring the foaming capacity of soaps and synthetic detergents. The structural and mechanical properties were determined using a Brookfield DV-II + PRO viscosimeter (USA) with a rotary adapter with a coaxial cylinder system. The pH value of the investigated foam samples was determined potentiometrically. Results and Discussion: Based on the carried out physical, chemical and technological research, the composition of the foam base was substantiated at an acidic pH value: disodium laureth sulfosuccinate - 20.0%, cocamidopropyl betaine - 6.0%, cocoglycoside glyceryl oleate - 1.0%, PEG-7 glyceryl cocoa - 0, 5%, PEG-150 polyglizeril-2 stearate and laureate-3-0.4%, rapeseed oil ethoxylated amide - 1.0%, hydroxypropyl methylcellulose - 0.1%, glycerol - 1.0%, sodium chloride - 1.6, lactic acid with pH values up to 3.5-4.0, purified water up to 100.0%. Conclusions: Structural-mechanical studies established that this foam base with a number of modern detergents was characterized by a pseudo-plastic type of flow, the structural viscosity of which was equal to 10,200 mPa • s (at 20 r.p.m.), that corresponds to the regulated requirements in accordance with the current normative documentation.